Treatment and outcomes of metastatic colorectal cancer patients in public and private hospitals: results from the South Australian Metastatic Colorectal Cancer Registry. Issue 1 (11th February 2021) - McNeill, David; Karapetis, Christos S.; Price, Timothy J.; Meagher, Philip; Piantadosi, Cynthia; Quinn, Stephen; Roder, David; Padbury, Rob; Maddern, Guy; Townsend, Amanda; Jayawardana, Madawa W.; Roy, Amitesh C.
Abstract: Background: Studies have reported significant differences in baseline characteristics and outcomes of metastatic colorectal cancer (mCRC) patients when managed in private versus public hospitals. Aims: To compare disease, treatment and survival outcomes of patients with mCRC in public versus private hospitals in South Australia (SA). Methods: Analysis of prospectively collected data from the SA mCRC Registry. Patterns of care and outcome data according to location of care and socioeconomic status based on Index of Relative Socio‐Economic Advantage and Disadvantage were analysed. Results: A total of 3470 patients' data was analysed during February 2006–January 2015. The majority (70%) of patients received treatment in public hospitals. Patients in the upper 50% for Index of Relative Socio‐Economic Advantage and Disadvantage score were more likely to receive treatment at a private hospital (41.2% vs 21.56%) compared to <50%. Public patients had higher burden of disease (10.49% vs 7.41%, P = 0.005). Public patients received less treatment compared to the private patients (odds ratio = 0.48 (0.38–0.61), P = 0.01) and rates of surgical resections were lower in public patients. After adjusting for the covariates, public patients survive 1.33 months ( P = 0.025) shorter than private patients with follow‐up time of 5 years. Patients receiving metastasectomy and more than three lines of treatment were shown to have the greatest survival benefit. Conclusion: Public patients have a higher burden of disease and in comparison are less likely to receive systemic therapy and have lower survival than patients treated in private hospitals.